Correlation between nurses' self-compassion, mental state and job burnout - Han Lingyu; Ronnell D. Dela Rosa (Northern Negros State College of Science and Technology (NONESCOST), 2021)
With the development of society, the demands of patients for various nursing services are increasing, and the shortage of nurses does not match, which leads to negative emotions such as anxiety, depression, and job burnout among nurses. This study sought to investigate the status quo of job burnout of clinical first-line nurses and analyzes the relationship between self-compassion, mental state, and job burnout. The study is descriptive and the survey site is in a Chinese hospital. Using the convenience sampling method, 222 clinical nurses in the third-level general hospital of Henan Province were selected as the subjects of this study. The survey was conducted using a general data survey form, Nurse Burnout Scale, Self-Compassion Scale, and Symptom Self-Rating Scale (SCL-90), Data were analyzed using frequency counts, percentages, mean, and Pearson Product Moment Correlation statistics. Based on the findings, The influence model of self-help on SCL-90 and the relationship between emotional exhaustion and personal achievement is the indirect mediation model, while the influence model of self-help on SCL-90 and the relationship of individuation is the complete mediation model. The survey results are intended to provide a theoretical basis for nursing managers to take preventive measures in advance to reduce nurses' job burnout.